Comparative analysis of mesenchymal stem cells cultivated in serum free media - Lee, Joo Youn; Kang, Min Hee; Jang, Ji Eun; Lee, Jeong Eon; Yang, Yuyeong; Choi, Ji Yong; Kang, Hong Seok; Lee, Uiil; Choung, Ji Woong; Jung, Hyeryeon; Yoon, Young Chan; Jung, Kyung Hee; et al. (Scientific Reports, 2022)
Stem cells are attractive candidates for the regeneration of tissue and organ. Mesenchymal stem cells (MSCs) have been extensively investigated for their potential applications in regenerative medicine and cell therapy. For developing effective stem cell therapy, the mass production of consistent quality cells is required. The cell culture medium is the most critical aspect of the mass production of qualified stem cells. Classically, fetal bovine serum (FBS) has been used as a culture supplement for MSCs. Due to the undefined and heterologous composition of animal origin components in FBS, efforts to replace animal-derived components with non-animal-derived substances led to safe serum free media (SFM). Adipose derived mesenchymal stem cells (ADSCs) cultivated in SFM provided a more stable population doubling time (PDT) to later passage and more cells in a shorter time compared to FBS containing media. ADSCs cultivated in SFM had lower cellular senescence, lower immunogenicity, and higher genetic stability than ADSCs cultivated in FBS containing media. Differential expression analysis of mRNAs and proteins showed that the expression of genes related with apoptosis, immune response, and inflammatory response were significantly up-regulated in ADSCs cultivated in FBS containing media. ADSCs cultivated in SFM showed similar therapeutic efficacy in an acute pancreatitis mouse model to ADSCs cultivated in FBS containing media. Consideration of clinical trials, not only pre-clinical trial, suggests that cultivation of MSCs using SFM might offer more safe cell therapeutics as well as repeated administration due to low immunogenicity.
Keywords: Acute Disease; Animals; Cell Differentiation; Cell Proliferation; Cells, Cultured; Culture Media; Culture Media, Serum-Free; Mesenchymal Stem Cells; Mice; Pancreatitis; Serum